2014
DOI: 10.1007/s11105-014-0825-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Two-Component System–Related Drought-Responsive Genes in Two Contrasting Drought-Tolerant Soybean Cultivars DT51 and MTD720 Under Well-Watered and Drought Conditions

Abstract: Two-component systems (TCSs) have been shown to participate in plant responses to drought. In this study, results of real-time quantitative PCR (RT-qPCR) of 26 selected dehydration-responsive TCS-related genes in roots and shoots of two Vietnamese soybean cultivars (DT51 and MTD720) with contrasting drought-tolerant phenotypes suggest a positive correlation between the number of droughtinducible TCS genes and their drought-tolerant ability. In addition, expression analyses of the roots and shoots indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
(94 reference statements)
1
13
0
Order By: Relevance
“…In part of this study, transcripts of two GmHP genes (GmHP03 and GmHP06) displayed higher levels under dehydration treatment [98]. Consistent with these reports, Thu et al (2015) found that GmHK07 was potentially associated with an enhanced drought tolerance phenotype after performing comparison in expression profiles of dehydration-responsive TCS genes between two Vietnamese soybean cultivars with contrasting drought-tolerant phenotypes [99]. Although more experimental evidence, such as in planta studies, is needed to support mechanistic models of GmHK07, it seems reasonable to assume that GmHK07 might be a key component in mediating drought tolerance in soybean.…”
Section: Response Of Ck Signaling Genes To Drought Stresssupporting
confidence: 90%
“…In part of this study, transcripts of two GmHP genes (GmHP03 and GmHP06) displayed higher levels under dehydration treatment [98]. Consistent with these reports, Thu et al (2015) found that GmHK07 was potentially associated with an enhanced drought tolerance phenotype after performing comparison in expression profiles of dehydration-responsive TCS genes between two Vietnamese soybean cultivars with contrasting drought-tolerant phenotypes [99]. Although more experimental evidence, such as in planta studies, is needed to support mechanistic models of GmHK07, it seems reasonable to assume that GmHK07 might be a key component in mediating drought tolerance in soybean.…”
Section: Response Of Ck Signaling Genes To Drought Stresssupporting
confidence: 90%
“…Drought is a type of dehydration stress and largely restricts crop productivity and quality. Improving crop tolerance to drought stress is an effective strategy for the promotion of sustainable agriculture in most crop production regions worldwide [1]. There has been extensive research on plant responses to drought stress at the morphological [2–6], physiological [2, 7–15], and biochemical [1621] levels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided strong lines of evidence for the participation of the soybean type-C RR gene GmRR34 in drought stress responses [35,36]. According to these reports, expression of GmRR34 was markedly up-regulated in root and/or shoot tissues under drought [36] and dehydration [35]. Furthermore, sequence analysis of GmRR34 recognized a cis-motif MYCR (myelocytomatosis-related protein recognition site) in its 1000-bp promoter region [30].…”
Section: Discussionmentioning
confidence: 98%
“…Among these genes, GmRR34, a type-C RR, was found to be intensively induced upon exposure to 10-h-dehydration treatment. A subsequent study of TCS genes using Vietnamese drought-tolerant and drought-sensitive soybean cultivars revealed nine genes (i.e., 2 HK-, 1 HP-, and 6 RR-encoding genes) that might have positive involvement in mediating plant adaptation to water-deficit conditions, as their expression levels were enhanced significantly in the former cultivar [36]. Interestingly, GmRR34 was also a member of this candidate list.…”
Section: Introductionmentioning
confidence: 99%